Evaluasi dan Perbaikan Antarmuka Pengguna Kursus Perpajakan Daring Piranha Smart Center dengan Pendekatan Human-Centered Design - Mohamad Zakaria Al Ansori; Retno Indah Rokhmawati; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. Piranha Multi Talenta develops a learning management system Piranha Smart Center as a taxation education course or called website of LMS PSC. Although website LMS PSC has been used by course participants, some issues related to the interface are still found while accessed by smartphone. This study applies Human-Centered Design (HCD) as developing design solutions and using usability testing to find out the interface evaluation value and user experience. User interface evaluation was carried out twice, which are before and after improvement of the user interface LMS PSC. The first evaluation is carried out to understand the context of use and to validate the problems. In the first evaluation which was followed by five participants obtained the average value of effectiveness is 88%, the average value of efficiency is 0,0251 goals/second and 83,19%, and the user satisfaction value based on SEQ is around 3,6 to 5,2 and based on SUS score is 57,00 (level D). Moreover, user interface improvement has been carried out intending to resolve user problems and increase the usability aspects. In the evaluation of user interface improvement that was done as many as two sessions and followed by five previous participants with the same task scenario when the initial evaluation task scenario can improve the value of effectiveness to 100%, the value of efficiency to 0,0574 goals/second and 100%, the increase of user satisfaction value based on SUS score is 94,00 (level A+) and SEQ scores are around 6,4 to 7. While the usability value with task scenario regarding the need for new features that found when understanding the context of using earn effectiveness value about 93%, efficiency value are 0,0771 goals/second and 93,26%, user satisfaction based on SUS score is 90,00 (level A+) and SEQ scores are around 6,6 to 6,8.